The Impact of the COVID-19 Pandemic on Informal Caregivers of People With Parkinson's Disease Residing in the UK: A Qualitative Study. (May 2023) - Rippon, Daniel; Hand, Annette; Dismore, Lorelle; Caiazza, Roberta
Informal caregivers can experience various demands when providing care and support for People with Parkinson's disease (PwP) in their own homes. The outbreak of SARS-CoV-2 and public health strategies employed to mitigate the spread of COVID-19 have presented challenges to the general populace on a global basis. The present study used a qualitative research design to explore how the COVID-19 pandemic has impacted informal caregivers in their role of providing care for PwP in their own homes. A series of 1:1 semi-structured interviews were conducted with 11 informal caregivers of PwP ( M age = 72.64 years, SD = 8.94 years). A thematic analysis indicated that 1) vulnerabilities to COVID-19, 2) home maintenance & activities of daily living and 3) engagement with healthcare services were 3 themes that provided indications on how the COVID-19 pandemic impacted informal caregivers of PwP. The present study provides illustrations of how being an informal caregiver of PwP and being identified as high risk to COVID-19 can present challenges to the process of caring for loved ones who are also vulnerable to SARS-CoV-2. The results of the present study highlights the necessity to develop strategies to ensure that informal caregivers have the necessary resources to provide care for PwP in their homes and also maintain their own well-being in the post COVID-19 era.